1983
DOI: 10.1073/pnas.80.15.4813
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement and amplification of c-abl sequences in the human chronic myelogenous leukemia cell line K-562.

Abstract: Structural rearrangements of specific cellular sequences (c-onc genes) homologous to acute transforming retrovirus oncogenes (v-onc genes) have been recently described in various malignancies. Here we show that human cellular sequences (c-abl) homologous to the transforming sequences of the mouse Abelson leukemia virus (v-abl) are amplified some 4-to 8-fold in K-562, a Philadelphia chromosome-positive cell line derived from a patient with chronic myelogenous leukemia in blast crisis. Restriction analysis of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(65 citation statements)
references
References 33 publications
0
64
0
Order By: Relevance
“…The cells in this clone contained one copy of the BCR-ABL gene and were highly skewed towards an erythroid differentiation program. The level and degree of phosphorylation exhibited by the p210 BCR-ABL expressed in these cells was equivalent to that seen in K562 cells, a cell line developed from a CML patient with blast phase disease that contains multiple copies of the BCR-ABL oncogene 21,22 and also displays evidence of erythroid differentiation. 23 Thus, some of the features obtained in this in vivo xenograft model are more reminiscent of blast phase CML where higher levels of BCR-ABL expression are typically seen 24,25 and perturbations of differentiation are usually more exaggerated.…”
Section: Discussionmentioning
confidence: 94%
“…The cells in this clone contained one copy of the BCR-ABL gene and were highly skewed towards an erythroid differentiation program. The level and degree of phosphorylation exhibited by the p210 BCR-ABL expressed in these cells was equivalent to that seen in K562 cells, a cell line developed from a CML patient with blast phase disease that contains multiple copies of the BCR-ABL oncogene 21,22 and also displays evidence of erythroid differentiation. 23 Thus, some of the features obtained in this in vivo xenograft model are more reminiscent of blast phase CML where higher levels of BCR-ABL expression are typically seen 24,25 and perturbations of differentiation are usually more exaggerated.…”
Section: Discussionmentioning
confidence: 94%
“…3,5 Although amplification of the BCR/ABL fusion gene has been described in cases of chronic myeloid leukemia (CML) treated with imatinib mesylate, seen both as HSRs 6 and dmins, 7 amplification of ABL alone is rare. A six-fold and a 15-fold amplification of the gene have been described in the CML-derived cell line, K562, 8 and in a patient with CML in lymphoid blast crisis, respectively. 9 The only other FISH report of amplification involving ABL was in three cases of secondary AML.…”
Section: To the Editormentioning
confidence: 99%
“…K562 is known to have an approximately six-fold amplification of ABL. 8 In our patient sample (3183), ABL was amplified at least five-fold in comparison with K562, taking into consideration that only 67% of the cells within the bone marrow sample showed evidence of amplification. Examination of the ethidium bromide gel confirmed that the increased signal intensity in K562 and patient 3183 was not a loading artefact.…”
Section: To the Editormentioning
confidence: 99%
“…In the HL-60 myeloid cell line and in fresh leukemia cells from patients, c-myc was reportedly amplified [21,22]; it was also amplified in one case of CML during progression from chronic to acute phase [23] and in [24]. Several authors have reported amplification of c-abl in K562, an erythroleukemia cell line containing the t(9;22) translocation typical of CML [25]. In K562, the amplification unit of the translocated c-abl involves the Ig lambda light-chain constant region (Ch), implying that the amplification occurred subsequent to translocation of c-abl from chromosomes 9 to 22, the map site of Ch [26].…”
Section: Dnamentioning
confidence: 99%